PENGARUH PEMASARAN DIGITAL DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN IN-HOUSE EVENT DI SEMINYAK, BALI - I Nengah Wirata (JURNAL KEPARIWISATAAN, 2021)
Through digital marketing, hotels in Seminyak publish their products in the form of in-house events with interesting themes to welcome New Year's Eve. On average they publish it on social media, this aims to facilitate promotion and streamline the time, effort, and costs incurred during the promotion process. The research objective was to examine how digital marketing and brand image influence purchasing decisions at home events in the Seminyak Bali area. The number of samples used was 182 respondents with the purposive sampling technique. Data processing is used with multiple linear regression analysis in the SPSS version 23. The results show that there is a partial positive relationship with digital marketing (X1) 3.151 with a significantly less than the ? value (0.002 <0.05), brand image of 5.999 with less significance. from the value of ? (0.000 <0.05) on the purchase decision at the event house in Seminyak, Bali. Simultaneously, digital marketing and brand image have a significant effect on purchasing decisions at home events in the Seminyak Bali area with a value of Fount greater than Fable, namely 98.458> 3.05 and a significance value of 0.000.